The relationship between social support and erectile dysfunction in middle-aged and older males - Hu, Danqing; Zhang, Yan; Zhang, Yue; Liu, Yu; Han, Jing (Frontiers in Public Health, 2024)
Background Erectile dysfunction (ED) is a prevalent condition that affects middle-aged and older men, impacting their sexual health and overall wellbeing. We aimed to investigate the relationship between social support and ED among this specific population. Methods Data were collected from the National Health and Nutrition Examination Survey. Social support was assessed through various dimensions, including emotional support, material support, and network support. Multivariate logistic regression was performed to examine the association between social support and ED, and a propensity-score-matched (PSM) analysis was further conducted. Results Among 1938 middle-aged and older males in the United States, 49.9% had a history of ED. ED was more prevalent in older individuals and those with comorbidities such as hypertension, prostate disease, higher serum creatinine level, and mental problems. Males with lower social support scores had a higher weighted rate of ED (P < 0.001). After adjusting for multiple variables in logistic regression analysis, a higher social support score was associated with a 19% lower likelihood of ED (weighted odds ratio [OR] 0.81, 95% confidence interval [CI] 0.66–0.98, P = 0.032). The association remained consistent after propensity score matching (OR 0.80, 95% CI 0.66–0.98, P = 0.028). Conclusion Social support appears to be associated with a reduced risk of ED in middle-aged and older men. Further research is needed to better understand this relationship and explore interventions that enhance social support, potentially leading to improved sexual health outcomes.